Are tomorrow's doctors prepared to prevent dementia? A cross-sectional study of Tasmanian medical students' knowledge of dementia risk factors. (February 2022) - Morgan, J.; Bindoff, A.; Doherty, K.; Vickers, J.; Alty, J.
Highlights: Prevention is the key strategy to reduce rising dementia incidence globally. 40% dementia cases are attributable to modifiable risk factors and doctors have key role in managing these. Medical student general knowledge of dementia improves with years of education. Specific knowledge of modifiable dementia risk factors remains limited. Recognition of vascular risk factors for dementia was particularly poor. Abstract: Tomorrow's doctors are unprepared to prevent dementia. This cross-sectional study invited medical students enrolled in the University of Tasmania 5-year medical degree (MBBS) to participate in an online questionnaire during 2019. This study measured students' recall of risk factors, prompted and unprompted, for dementia and cardiovascular disease (CVD), and Dementia Knowledge Assessment Scale (DKAS) score. Data were collected via an online survey comprising the DKAS, and risk factor questions adapted from the Alzheimer's Research UK National Monitor Survey, with questions on CVD risk factors added for comparison. Medical students (n = 82) proffered fewer unprompted risk factors for dementia than for CVD and were less proficient at recognizing dementia risk factors from a prompted list. Knowledge of vascular risk factors for dementia was particularly limited. Their broader dementia knowledge was generally adequate and DKAS scores were at the level of a qualified doctor by final year. Whilst medical students' general knowledge of dementia was satisfactory, their knowledge of modifiable risk factors of dementia was limited. If replicated elsewhere, this raises concerns about whether the future medical workforce is equipped to take a necessary lead role in managing dementia risk reduction. As dementia incidence rises worldwide, and 40% cases are attributable to modifiable risk factors, educational programs may need to urgently address these deficiencies.